PEMBELAJARAN TEORI SASTRA BERBASIS DIGITAL DI ERA PANDEMI - Ahmad Bahtiar (KOLASE, 2022)
ABSTRACT The presence of the corona virus or Covid-19 has made life not as normal as it used to be. Some of the impacts given by Covid-19 are quite influential, one of which is in the education sector. This influence has an impact that makes educators change existing teaching strategies into digital-based teaching strategies in the pandemic era. Lecturers feel that using rote-based theoretical learning techniques makes the scope of the class ineffective but does not produce students who have critical and creative thinking in the current pandemic era. The purpose of this research entitled "Digital-Based Literary Theory Learning in the Pandemic Era" is to provide an overview and explanation of the application of digital-based learning in literary theory courses in the pandemic era. This study uses a descriptive research method with a qualitative approach to explain and find out how effective this digital-based learning is if it is applied and implemented in learning using digital media. The results of this digital-based learning research provide new experiences for lecturers in managing classes and produce students who are effective, innovative, and creative in learning, one of which is by publishing popular articles and infographics. It can be concluded that one of the efforts to overcome learning to be effective is to use digitalization-based learning methods by increasing creativity. Keywords: Literary Theory, Digital-Based Learning, Digital Media, Covid-19 ABSTRAK